Expression Profile of Hydroxysteroid Dehydrogenase-like 2 in Polychaete Perinereis aibuhitensis in Response to BPA - Yingpeng Li; Huan Zhao; Min Pang; Yi Huang; Boxu Zhang; Dazuo Yang; Yibing Zhou (Life, 2022)
Hydroxysteroid dehydrogenases (HSDs) play an important role in the metabolism of steroids and xenobiotics. However, the function of HSDs in invertebrates is unclear. In this study, we cloned the hydroxysteroid dehydrogenase-like 2 (HSDL2) gene in Perinereis aibuhitensis, which is 1652 bp in length, encoding 400 amino acids. This sequence contains conserved short-chain dehydrogenase and sterol carrier protein-2 domain, and the alignment analysis showed its close relationship with other invertebrate HSDL2. Further, the tissue distribution analysis of the HSDL2 gene showed it is expressed strongly in the intestine. The expression level of HSDL2 after inducement with bisphenol A (BPA) was also detected both at transcriptional and translational levels. The results inferred that BPA exposure can induce HSDL2 expression, and the inductive effect was obvious in the high-concentration BPA group (100 μg/L). In summary, our results showed the detoxification function of HSDL2 in polychaetes.